Effectiveness and mechanism for the simultaneous adsorption of Pb(II), Cd(II) and As(III) by animal-derived biochar/ferrihydrite composite. (April 2022) - Hong, Chengyi; Dong, Zhiqiang; Zhang, Jichen; Zhu, Ling; Che, Lei; Mao, Fuzhi; Qiu, Yuping
Abstract: The emerging animal-derived biochar (AB) has shown potential for mitigating the contamination of cationic heavy metals, but has no affinity to oxyanionic metals. In this study, we developed an AB/ferrihydrite composite with a AB/Fe mass ratio of 4.0 (ABF-4) for the simultaneous adsorption of cationic Pb(II)/Cd(II) and anionic As(III). ABF-4 is a type of hydroxyapatite-rich biochar coated with nanoscale iron hydroxide aggregates. The adsorption of Pb(II), Cd(II), and As(III) on ABF-4 were 2.64, 1.55, and 0.48 mmol/g, and were 135%, 150%, and 4500% higher than those of pure AB, respectively. The enhanced adsorption of Pb(II) and Cd(II) by ABF-4 is partially due to the increase in surface area and micropores. The nano-sized ferrihydrite on ABF might help form surface complexation with As(III) and oxidize As(III) to As(V). In multimetal systems, Pb(II) and Cd(II) can promote As(III) adsorption due to the formation of NaPb4 (AsO4 )3 precipitate and the ternary complex of arsenite and cadmium with ABF-4, whereas Cd(II) adsorption might be inhibited because of the surface coverage of Pb5 (PO4 )3 Cl precipitate on ABF-4. However, the coexistence of Pb in soils does not influence the immobilization of Cd. The amendment of ABF-4 can considerably decrease the availability of Pb, Cd, and As in soils from Pb–Zn smelting sites. Hence, ABF-4 is a promising multifunctional material for the potential immobilization of multicomponent heavy metals. Graphical abstract: Image 1 Highlights: ABF-4 is an animal-derived biochar with surface-loaded nano-ferrihydrite. ABF-4 exhibits the enhanced adsorption of single-metal Pb(II), Cd(II), and As(III). Pb(II) promotes As(III) adsorption due to the formation of NaPb4 (AsO4 )3 precipitate. Cd(II) induces As(III) to form ternary complex for enhancing As(III) adsorption. ABF-4 effectively decreases the availability of Pb, Cd, and As in soils.